Locomotory behaviour of two phylogenetically distant predatory ciliates: does evolutionary history matter?. Issue 3 (4th May 2018) - Bohatová, Michaela; Vďačný, Peter
Abstract : Ciliates are unicellular eukaryotic microorganisms that express their behaviour by motion. In this study, the authors attempt to address the question of whether locomotion could reflect evolutionary history or whether it instead depends on cell geometry and/or lifestyle. To this end, the authors investigated locomotory behaviour of two predatory ciliates, Coleps hirtus and Spathidium muscicola . Both exhibit similar cell geometry (bursiform, holotrichously ciliated body with apical oral apparatus), but are phylogenetically distant. Their motion was video recorded, trajectories were digitalised and their qualitative and quantitative elements determined and evaluated. Motion of both species consisted of long-lasting elements that enable spatial distribution and of short-lasting elements that serve for direction change. Both species shared four types of long-lasting elements: meandering; twisting; spinning; and helical motion. Coleps hirtus additionally performed pseudohelical movement and S. muscicola conducted conical locomotion. The common types of short-lasting elements were: stop and reorientation reaction; side-stepping reaction; wide side-stepping reaction; and side-stepping reaction with long backward motion. Spathidium muscicola additionally performed a prolonged side-stepping reaction. Statistical analyses revealed significant differences between the two species in 12 out of 26 motion parameters. In multivariate analyses based on 35 quantitative, 12 derived ratios and 3 qualitative variables, both taxa formed homogenous and distinctly separated groups, documenting that interspecies differences are bigger than intraspecies ones. Comparative analyses uncovered that the locomotory behaviour of C. hirtus is most similar to that of Tetrahymena species which are filter feeders with a ventrally located oral apparatus. The locomotion of S. muscicola most resembles that of Litonotus lamella, a lanceolate predator with ventrally extending oral apparatus. Since Coleps and Tetrahymena belong to two closely related classes, Prostomatea and Oligohymenophorea respectively, and since Spathidium and Litonotus belong to the same class Litostomatea, the authors argue that their locomotory behaviour reflects evolutionary history rather than cell geometry and/or predatory lifestyle.